The Greek Crisis: Causes and Implications - Kouretas, Georgios P.; Vlamis, Prodromos (Panoeconomicus, 2010)
This paper presents and critically discusses the origins and causes of the Greek fiscal crisis and its implications for the euro currency as well as the SEE economies. In the aftermath of the 2007-2009 financial crisis the enormous increase in sovereign debt has emerged as an important negative outcome, since public debt was dramatically increased in an effort by the US and the European governments to reduce the accumulated growth of private debt in the years preceding the recent financial turmoil. Although Greece is the country member of the eurozone that has been in the middle of this ongoing debt crisis, since November 2009 when it was made clear that its budget deficit and mainly its public debt were not sustainable, Greece’s fiscal crisis is not directly linked to the 2007 US subprime mortgage loan market crisis. As a result of this negative downturn the Greek government happily accepted a rescue plan of 110 billion euros designed and financed by the European Union and the IMF. A lengthy austerity programme and a fiscal consolidation plan have been put forward and are to be implemented in the next three years.Key words: Sovereign risk, Debt crisis, Bonds market, Expectations, Fiscal guarantees.JEL: F34, G01, G15.